The Production and Dissemination of Knowledge in Mahesh Bikram Shah's Short Story "Chapamarko Chhoro" - Pokharel, Ranjita (Medha: A Multidisciplinary Journal, 2025)
This article focuses on analyzing cultural representation within Mahesh Bikram Shah's short story collection, specifically the titular story "Chapamarko Chhoro". Employing a qualitative research methodology, text-centric analysis, and a critical and analytical framework, this study draws upon materials collected from various libraries. The theoretical foundation of this article rests on cultural studies, particularly the concept of representation. Cultural representation has emerged as a distinct and evolving methodology in literary studies, examining the interplay between cultural forms presented in literary texts and prevailing cultural values within society. As an interdisciplinary field, cultural studies integrates theoretical bases, concepts, and methodologies from diverse academic domains. While acknowledging the multifaceted nature of cultural studies, this article primarily analyzes the story's depiction of class and gender representation, authorial ideology, and hegemony. Reflecting the class structure of Nepali society, the narrative presents a struggle against state power and a revolutionary class leadership. It portrays the state, through its oppressive apparatus of the police administration, controlling and arresting family members, particularly women. The story powerfully depicts both class and gender representation, with strong roles for both the ruling and the ruled classes. Observing the actions of the guerrilla's son, which initially sought to establish hegemony through coercion and later through consensual means, the narrator's evolving perspective on the guerrilla contributes to knowledge production, suggesting that the author's viewpoint is not entirely neutral.